Pengembangan Sistem Informasi Keuangan Digital Berbasis Budgeting & Financial Planning - Panggabean, Christian Vanesta; Sinaga, Ridwan Niko; Arrazi, Dhiemaz Aditya; Haryono, Wasis (CV. ITTC INDONESIA, 2026)
Unstructured financial management remains a major problem for many Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector. Ayam Goreng Karawaci, a culinary MSME, still uses manual financial records, which poses a risk of recording errors, late reporting, and difficulty in monitoring financial conditions in real time. This study aims to design an automated budget planning, cash flow recording, and financial reporting system that can improve the efficiency and accuracy of financial management. The research methods used include observation, interviews, and documentation studies, as well as a Unified Modeling Language (UML)-based system design approach. The results show that the automated financial system can simplify transaction recording, reduce calculation errors, and produce financial reports quickly and accurately. The implementation of this system is expected to assist MSMEs in making more informed business decisions based on valid financial data.